2007
DOI: 10.1017/s0265021506002250
|View full text |Cite
|
Sign up to set email alerts
|

Does dexmedetomidine reduce the injection pain due to propofol and rocuronium?

Abstract: Pretreatment with dexmedetomidine is not effective in reducing injection pain of propofol, but may attenuate the hand withdrawal associated to rocuronium, as lidocaine does.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
0
27
2
1
Order By: Relevance
“…The NRS pain score of uterine cramping after surgery in group SP and DP was significantly lower compared with group P after 30 min in PACU. In contrast to a study reporting that dexmedetomidine failed to reduce the injection pain of propofol [22], our study found a significantly lower NRS pain score associated with propofol injection in group DP compared with group P (P<0.001). The difference might be related to the increased duration (45 min) and dosage of dexmedetomidine (1 µg / kg) administered in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The NRS pain score of uterine cramping after surgery in group SP and DP was significantly lower compared with group P after 30 min in PACU. In contrast to a study reporting that dexmedetomidine failed to reduce the injection pain of propofol [22], our study found a significantly lower NRS pain score associated with propofol injection in group DP compared with group P (P<0.001). The difference might be related to the increased duration (45 min) and dosage of dexmedetomidine (1 µg / kg) administered in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Lidocaine pretreatment is one of the most commonly used therapeutic regimens for alleviating injection pain of propofol and rocuronium, and is as effective as dexmedetomidine [7,8]. However, the results of this study showed that lidocaine was not as effective as dexmedetomidine in every dose group.…”
Section: Discussioncontrasting
confidence: 60%
“…There have been a few studies of the effect of dexmedetomidine on pain associated with injection of rocuronium and propofol [6][7][8]. In these studies, dexmedetomidine was injected after squeezing the forearm with a tourniquet to a pressure of 70 mmHg to ensure transient localization of dexmedetomidine in the vein.…”
Section: Discussionmentioning
confidence: 99%
“…Propofolün soğuk uygulanması (4°C), ısıtılarak (37°C) uygulanması, propofol infüzyonunun seyreltilmesi, taşıyıcı infüzyon sıvısının hızının değiştirilmesi (4) , lidokain, nonsteroidal antiinflamatuvar ilaçlar (5,6) , granisetron (1) , metoklopromid (7) , opioidler (8) , hidrokortizon (9) , deksmedetomidin (10) , magnezyum sülfat (11) , efedrin (12) ve kısa etkili beta-bloker (13) ile öntedavi, oral klonidin verilmesi bunlardan bazılarıdır. Bu uygulamaların bir kısmı etkisiz kalırken bir kısmı da ağrıyı tamamen engelleyememiş ancak, ağrı insidansını ve yoğunluğunu azaltmıştır.…”
Section: Discussionunclassified